A preface to marketing management - Peter, J. Paul, author; Donnelly, James H., Jr., author (New York : McGraw-Hill Education, 2019)
The content of all formats are the same. Preface to Marketing Management, 15e, by Peter and Donnelly, is praised in the market for its clear and concise presentation of the basic principles of marketing in such a way that the core concepts and ideas are covered in sufficient depth to ensure understanding. By offering an engaging, clear, and conceptually sound text, this book has been able to maintain its position as a leading marketing management text. The fifteenth edition serves as an overview for critical issues in marketing management. Its brief, inexpensive, paperback format makes it a perfect fit for instructors who assign cases, readings, simulations or offer modules on marketing management for MBA students. The text also works in courses that implement a cross-functional curriculum where the students are required to purchase several texts.
Includes bibliographical references and index.
English text.
Keywords: Marketing -- Management